Frustrated magnetism and dynamical properties in pyrochlore-type magnet Dy2Ti2−xFexO7 - Liu, Hui; Zou, Youming; Ling, Langsheng; Zhang, Lei; Tong, Wei; Zhang, Changjin; Zhang, Yuheng (Journal of magnetism and magnetic materials, 2014)
We have studied the magnetic and dynamical properties of spin-frustrated magnet Dy2Ti2−x FexO7 single crystals. Bulk magnetization data of the heavily Fe doped samples give a negative Curie–Weiss temperature, probably suggesting the existence of short-range antiferromagnetic interaction in Fe-doped samples. Dynamical analyses show that the doped system still freezes into an ice-like state but it is more dynamical than that in pure spin ice Dy2Ti2O7. Furthermore, the dynamic freezing of the spins is suppressed to lower temperatures, which is caused by the Dy-Fe spin interactions and the altered crystalline electric field. It is also found that the coordination number of Fe decreases at high doping level (x=0.15), leading to the change of the spin state of Fe3+. •Doped system Dy2Ti2−xFexO7 still freezes into an icelike state.•Doped system is more dynamical than that in pure spin ice Dy2Ti2O7.•The dynamic freezing of the Dy3+ spins is suppressed to lower temperatures.•The spin configuration of Fe3+ becomes high-spin state at high doping level.